Bandwidth Optimization Techniques in Heterogeneous 5G Networks Using DUDe - Konstantinos Tsachrelias; Chrysostomos Katsigiannis; Vasileios Kokkinos; Apostolos Gkamas; Christos Bouras; Philippos Pouyioutas (The 6th International Conference on Advanced Communication Technologies and Networking (CommNet 2023), December 11 – 13, 2023, Rabat, Morocco, 2023)
The deployment of 5G networks has led to a significant increase in demand for high-speed data rates and improved overall network performance. HetNets are a promising solution for providing coverage and capacity enhancements for 5G networks. However, one of the key challenges in HetNets is the optimization of bandwidth allocation. Traditional resource allocation techniques are limited in their ability to provide efficient and effective solutions for 5G networks. To address this challenge, a novel technology called DUDe (Downlink/Uplink Decoupling) has been proposed. DUDe optimizes bandwidth allocation in HetNets by dynamically adjusting the allocation of network resources to user demand and network conditions. The motivation of this paper is to highlight the importance of DUDe technology in macro cell offloading in 5G HetNets. The paper evaluates the performance of DUDe in comparison to traditional resource allocation techniques and provides insights into the key factors that influence its effectiveness. Moreover, this paper presents a detailed analysis of simulations results and provides recommendations for future research. The findings of this study will be useful for network operators and researchers in developing more efficient and effective resource allocation strategies for 5G networks.